2011
DOI: 10.1165/rcmb.2009-0182oc
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt Protects Alveoli from Neonatal Oxygen-Induced Lung Injury

Abstract: Bronchopulmonary dysplasia (BPD) is the main complication of extreme prematurity, resulting in part from mechanical ventilation and oxygen therapy. Currently, no specific treatment exists for BPD. BPD is characterized by an arrest in alveolar development and increased apoptosis of alveolar epithelial cells (AECs). Type 2 AECs are putative distal lung progenitor cells, capable of regenerating alveolar homeostasis after injury. We hypothesized that the protection of AEC2 death via the activation of the prosurviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…However, the restoration of Akt just to the "normal" level after cessation of cigarette smoking does not appear sufficient for repair of damaged lung because the significant emphysematous change was still observed in the SM rat lungs in our previous study (18). Consistent with this idea, forced expression of active Akt in vivo resumed alveolar development in a bronchopulmonary dysplasia model caused by hyperoxia, which resulted in p-Akt reduction (2).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, the restoration of Akt just to the "normal" level after cessation of cigarette smoking does not appear sufficient for repair of damaged lung because the significant emphysematous change was still observed in the SM rat lungs in our previous study (18). Consistent with this idea, forced expression of active Akt in vivo resumed alveolar development in a bronchopulmonary dysplasia model caused by hyperoxia, which resulted in p-Akt reduction (2).…”
Section: Discussionmentioning
confidence: 76%
“…It also promotes cell proliferation by inhibiting interaction of p21 with PCNA and promoting assembly of cyclin D1:cyclin-dependent kinase 4 complex. Of note, a pathological significance of Akt in maintenance of alveolar architecture is evidenced by the findings that inhibition of the PI3K/Akt pathway by wortmannin aggravated hyperoxia-induced bronchopulmonary dysplasia, and forced expression of constitutively active Akt attenuated hyperoxia-induced airspace enlargement with suppression of apoptosis (2). However, although the authors showed that adenoviral expression of Akt attenuated hyperoxia-induced lung injury and rescued type 2 alveolar epithelial cells from hyperoxia-induced apoptosis, it remains unknown whether Akt may play a critical role in survival, proliferation, and function in other cell types including lung fibroblasts for successful alveolarization.…”
Section: Discussionmentioning
confidence: 99%
“…important aspect of this pathological process involves cell death secondary to hyperoxia (6,28,29). Although a variety of mechanisms account for cell death in the lung (30), we decided to focus on the ER stress pathway, because limited information is available on this process in the context of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TTC3 appears to play an important role in cigarette smoke-mediated lung injury, possibly via Akt degradation, which may induce cell death and prevent lung repair through inhibition of cell proliferation. It is of note that patients with Down syndrome have alveolar hypoplasia (30) and that impaired alveolar development is associated with decreased Akt activation in a hyperoxia-induced bronchopulmonary dysplasia model (31).…”
Section: Discussionmentioning
confidence: 99%